The Rahmah El-Yunusiyah's Dedication in Islamic Education for Women in Indonesia - Rhoni Rodin; Miftahul Huda (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2020)
The history of Islamic education in Indonesia, apart from having a traditional character, not all women have had the opportunity to pursue education. The society paradigm considers that women are only weak creatures who do not need higher education. This has an impact on the role of women only in the domestic sphere, which does not have a broad role in the public sphere in society. Such social conditions moved the heart of a reformer figure in Islamic education from West Sumatra, named Rahmah el-Yunusiyah. The purpose of this study was to determine the sacrifice and struggle of Rahmah el-Yunusiah in the field of education and Rahmah el-Yunusiyah's views on the essence of Islamic religious education. She is the first female Islamic education figure to pay attention to the importance of education for women. She realizes that education is the main means to improve the position of women in the global life order. In this study using a qualitative approach. The method used is a research library. The data analysis technique used is content analysis. The result of this research shows that Rahmah el-Yunusiyah's dedication in Islamic education for women is that she founded the Diniyah school Puteri. According to him, religious education (Islam) according to him is the basis for the formation of human character, and becomes the essence for other activities. Keywords: Rahmah el-yunusiyah, Islamic education, Dedication a Good Women